Pathogenesis of Arterial Hypertension in the Pregnant Females - N. V. Kabanova (Общая реаниматология)
Objective: to study the pathogenetic mechanisms of development of arterial hypertension (AH) in pregnant females and to develop clinical and laboratory criteria that may determine the type of AH in them on the basis of a comprehensive study of hemostatic parameters.Subjects and materials. A hundred and seventy-two pregnant females with AH (a study group) and 54 healthy pregnant ones (a control group) were examined in the third trimester of pregnancy. In all, biochemical blood and urinary analyses determining the concentrations of urea, creatinine, sodium, and protein, followed by the calculation of partial renal functions, were made by the unified method. Enzyme radioimmunoassay was used to determine plasma renin activity. The concentrations of angiotensin-2, aldosterone, thyroxine-binding globulin, testosterone, estriol, estradiol, progesterone, and placental lactogen were measured by enzyme radioimmunoassay. Enzyme immunoassay was employed to estimate the levels of prostanoids. The activity of membranous lipid peroxidation was assessed by the level of its metabolites; the state of the antioxidative system was evaluated. The degree of endogenous intoxication was determined. Central hemodynamic parameters were estimated by tetrapolar rheography. Statistical processing used IBM 384/387 and the statistical package «Stadia».Results. Arterial hypertension caused by pregnancy was ascertained to involve pathogenetical-ly different types: low-, normal-, and high-renin ones. According to its type, the mechanisms of AH were variable. The pressor mechanisms in the pathogenesis of AH were sodium and water retention and elevated total peripheral resistance due to the activation of extrarenal (placental hormonal imbalance, increases in cortisol and angiotensin-2) and renal (increased ARP) pressor systems. The renal depressor system was presented by prostaglandins, the extrarenal depressor system by thyroxine.Conclusion. Activation of the extrarenal depressor system (elevated T4) was common in the pathogenesis of AH in the pregnant females. The knowledge of the pathogenetic mechanisms underlying the development of AH in pregnant females serves as the basis for working out a differential intensive care program.